Coxiella burnetii Whole Cell Vaccine Produces a Th1 Delayed-Type Hypersensitivity Response in a Novel Sensitized Mouse Model - Fratzke, Alycia P.; Gregory, Anthony E.; van Schaik, Erin J.; Samuel, James E. (Frontiers in Immunology, 2021)
Q-VAX®, a whole cell, formalin-inactivated vaccine, is the only vaccine licensed for human use to protect against Coxiella burnetii, the cause of Q fever. Although this vaccine provides long-term protection, local and systemic reactogenic responses are common in previously sensitized individuals which prevents its use outside of Australia. Despite the importance of preventing these adverse reactions to develop widely accepted, novel vaccines against C. burnetii, little is understood about the underlying cellular mechanisms. This is mostly attributed to the use of a guinea pig reactogenicity model where complex cellular analysis is limited. To address this, we compared three different mouse strains develop a model of C. burnetii whole cell vaccine reactogenic responses. SKH1 and C57Bl/6, but not BALBc mice, develop local granulomatous reactions after either infection- or vaccine-induced sensitization. We evaluated local and systemic responses by measuring T cell populations from the vaccination site and spleen during elicitation using flow cytometry. Local reaction sites showed influx of IFNγ+ and IL17a+ CD4 T cells in sensitized mice compared with controls and a reduction in IL4+ CD4 T cells. Additionally, sensitized mice showed a systemic response to elicitation by an increase in IFNγ+ and IL17+ CD4 T cells in the spleen. These results indicate that local and systemic C. burnetii reactogenic responses are consistent with a Th1 delayed-type hypersensitivity. Our experiments provide insights into the pathophysiology of C. burnetii whole cell vaccine reactogenicity and demonstrate that C57Bl/6 and SKH1 mice can provide a valuable model for evaluating the reactogenicity of novel C. burnetii vaccine candidates.